Hydrochemical, hydrophysical and sedimentological properties of the chimney mud of pockmark Chez-le-Bart (CB) in Lake Neuchatel, Switzerland in 2017 - Wirth, Stefanie B; Bouffard, Damien; Zopfi, Jakob (PANGAEA, 2020)
The pockmark mud, i.e. suspended sediment in the chimney, was sampled with a 5 l Niskin bottle (Hydro-Bios, Kiel) that was lowered from the boat to four depths within the chimney. For this we attached 20 kg of additional weight below the Niskin bottle and used two GoDevil messengers (2x 870 g; General Oceanics, Miami FL) to activate the closing mechanism of the bottle in the mud.
Keywords: chimney; Karst; Lake Neuchatel; LGD lacustrine groundwater discharge; Pockmark; ROV remotely operated vehicle; sediment fluidization; SGD submarine groundwater discharge